DETERIORATION OF VEGETABLE OILS EXPOSED TO DIFFERENT CONDITIONS OF STORAGE - Thode Filho, Sérgio; Cabral, Gabrielle Borges; Maranhão, Fabíola da Silveira; Sena, Marcelo Fonseca Monteiro; Silva, Elmo Rodrigues da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The final quality of the oil depends on all the stages of the production. These steps range from the cultivation, extraction, refining, transportation, distribution and marketing of oils. Oxidation processes in foods are responsible for reducing shelf life of raw materials and manufactured products leading to major economic loss. The objective of this study was to analyze the levels of acidity and peroxide virgin vegetable oils from soy, corn, canola and sunflower undergo under different conditions of storage before consumption. The procedure for checking the index of acidity and peroxide was conducted based on the methodology of the Adolfo Lutz Institute (2004). At the end of the analysis period, all oil exposed group had higher acid value and peroxide to the saved group. Soybean oil was found to be the most stable oil to work in relation to the indices evaluated, followed by sunflower oil. Despite the canola oil have low levels of saturated fatty acids, this research showed that canola oil is an extremely sensitive regarding their physicochemical stability when exposed to light and temperature.